T(1ρ) and T(2) relaxation times predict progression of knee osteoarthritis - Prasad, A.P. (2012)
OBJECTIVE: To evaluate whether T(2) and T(1ρ) relaxation times of knee cartilage determined with 3T magnetic resonance imaging (MRI) at baseline predict longitudinal progression of cartilage degenerative changes. METHODS: Quantitative analysis of cartilage was performed using 3T MRI with both T(2) and T(1ρ) mapping techniques in 55 subjects without evidence of severe osteoarthritis (OA) [Kellgren–Lawrence (KL) score of 0–3] at baseline. Morphological abnormalities of cartilage, menisci, ligaments and bone marrow were analyzed on sagittal fat-saturated intermediate-weighted fast spin echo (FSE) sequences. Progression of degenerative changes was analyzed over a period of 2 years. Progression was detected in 27 subjects while in 28 subjects no changes were found. Differences between T(2) and T(1ρ) relaxation times in these two cohorts were compared using one-way analysis of variance (ANOVA) and t tests. RESULTS: Baseline T(2) and T(1ρ) values were significantly higher in the progression cohort in all compartments (P < 0.05) except the lateral tibia (LT) for T(2) and the medial tibia (MT) for T(1ρ). Progression of cartilage degenerative disease was most pronounced at the medial femoral condyles and at the femoro-patellar joint; differences between the two cohorts for T(2) and T(1ρ) were also most significant in these compartments. CONCLUSIONS: T(2) and T(1ρ) measurements were significantly higher at baseline in individuals that showed progression of cartilage abnormalities over a period of 2 years and may therefore serve as potential predictors for progression of degenerative cartilage abnormalities in knee OA.